Participatory Agricultural Extention Model Toward Peatland Management In Term Of Prevention Peat And Forest Fires: Case Study on Sumatran Island, Indonesia - Suhaimi Ali, Arifudin; Roza Yulida; Besri Nasrul; Nurul Qomar; Yelly Zamaya (Tanjungpura International Journal on Dynamics Economics, Social Sciences and Agribusiness, 2022)
The participatory extension model in peatland management has not been available yet as a reference for the parties to prevent land and forest fires in Riau Province. Therefore, this study aims to offer a model of participatory agricultural extension in peatland management for the prevention of land and forest fires in Riau Province, Sumatran Island, Indonesia. A qualitative descriptive research method was used with a case study approach. In this study, two locations were chosen, Tualang Timur Village which is around Oil Palm Plantation and Tanjung Leban Village is located around the Industrial Plantation Forest. Data were collected by participatory observation, in-depth interviews, and FGD with parties representing the community, the business, and the government. Qualitative data analysis was done by data reduction, data presentation and conclusions. results show that participatory agricultural extension for the prevention of land and forest fires at the two research locations, both around oil palm plantations and industrial forest plantations, can be carried out in three approaches, namely land management, institutional strengthening, and community economic diversification. The participation of farmers in extension activities are involving in the planning, implementation and evaluation of agricultural extension programs. The role of participatory extension is in line with the extension's functions: education; dissemination of innovation; facilitation; consultation; supervision; monitoring and evaluation. Therefore, the participation approach are recommended on extension program in term of peatland fires prevention.